Benzodiazepine administration patterns before escalation to second‐line medications in pediatric refractory convulsive status epilepticus. (21st August 2021) - Sheehan, Theodore; Amengual‐Gual, Marta; Vasquez, Alejandra; Abend, Nicholas S.; Anderson, Anne; Appavu, Brian; Arya, Ravindra; Barcia Aguilar, Cristina; Brenton, J. Nicholas; Carpenter, Jessica L.; Chapman, Kevin E.; Clark, Justice; et al.
Abstract: Objective: This study was undertaken to evaluate benzodiazepine (BZD) administration patterns before transitioning to non‐BZD antiseizure medication (ASM) in pediatric patients with refractory convulsive status epilepticus (rSE). Methods: This retrospective multicenter study in the United States and Canada used prospectively collected observational data from children admitted with rSE between 2011 and 2020. Outcome variables were the number of BZDs given before the first non‐BZD ASM, and the number of BZDs administered after 30 and 45 min from seizure onset and before escalating to non‐BZD ASM. Results: We included 293 patients with a median (interquartile range) age of 3.8 (1.3–9.3) years. Thirty‐six percent received more than two BZDs before escalating, and the later the treatment initiation was after seizure onset, the less likely patients were to receive multiple BZD doses before transitioning (incidence rate ratio [IRR] = .998, 95% confidence interval [CI] = .997–.999 per minute, p  = .01). Patients received BZDs beyond 30 and 45 min in 57.3% and 44.0% of cases, respectively. Patients with out‐of‐hospital seizure onset were more likely to receive more doses of BZDs beyond 30 min (IRR = 2.43, 95% CI = 1.73–3.46, p  < .0001) and beyond 45 min (IRR = 3.75, 95% CI = 2.40–6.03, p  < .0001) compared to patients with in‐hospital seizure onset. Intermittent SE was a risk factor for more BZDs administered beyond 45 min compared to continuous SE (IRR = 1.44, 95% CI = 1.01–2.06, p  = .04). Forty‐seven percent of patients ( n  = 94) with out‐of‐hospital onset did not receive treatment before hospital arrival. Among patients with out‐of‐hospital onset who received at least two BZDs before hospital arrival ( n  = 54), 48.1% received additional BZDs at hospital arrival. Significance: Failure to escalate from BZDs to non‐BZD ASMs occurs mainly in out‐of‐hospital rSE onset. Delays in the implementation of medical guidelines may be reduced by initiating treatment before hospital arrival and facilitating a transition to non‐BZD ASMs after two BZD doses during handoffs between prehospital and in‐hospital settings.